Prevention and correction of hypocalaemia during systematic hypothermia in patients with aneurismal subarachnoid hemorrhages. - S. Dudukina (Medičnì Perspektivi, 2013)
The effectiveness of hypothermia as a method of neuroprotection in brain damage has been proved in many studies, but a large number of complications requires development of further protocols of its management. The article presents experience of treatment of aneurismal subarachnoid hemorrhage under conditions of preventive hypothermia. 84 patients were examined. In 56 of them the efficacy of developed method on prevention and correction of hypocalaemia developed as a result of cold diuresis has been proposed. It has been found that decrease in plasma potassium occurs in parallel with decrease in body temperature regardless the technique of potassium chloride injection. Introduction of potassium chloride solution in physiological dose of 0.2 mmol/kg prevents hypocalaemia development during preventive hypothermia. Injection of potassium chloride in the physiological dose of 0.2 mmol/kg/h and after beginning of patient’s rewarming – 0.8 mmol/kg within the period of one postsurgery day prevents the development of postoperative hypocalaemia in the postoperative period; and after patient’s rewarming– 0.8. mmol/kg within the period of one postoperative day prevents development of postoperative cardiac complications in the perioperative period by 20%.